Three new species of the fangblenny genus Meiacanthus from Indonesia, with color photographs and comments on other species (Teleostei: Blenniidae: Nemophini) - Smith-Vaniz, William F.; Allen, Gerald R. (Zootaxa, 2011)
Three new species of fangblennies are described from Indonesia. Meiacanthus abruptus is described based on two specimens, 31.4–36.6 mm SL, from Komodo Island and color photographs of others from Bali. The combination of a white or yellow body color and a single dark mid-lateral stripe that is bluntly rounded at its terminus on the caudal-fin base distinguishes it from other single striped species. This new species closely resembles the allopatric M. vicinus, which has the mid-lateral stripe extending farther onto the caudal fin and tapering to a point. Meiacanthus erdmanni is described from the only known specimen, 35.8 mm SL, photographed and collected in 65–70 m in Cenderawasih Bay, western New Guinea. One of the deepest known species of Meiacanthus, it has two dark mid-lateral stripes and differs from other doublestriped species in having a series of dark blotches on the base of the dorsal fin and only 24 segmented dorsal-fin rays. Meiacanthus cyanopterus, another deep-water species, is described from seven specimens, 19.8–45.3 mm SL, collected in 40–65 m at three sites in Alor Strait. In life this species has a dorsal fin with a blue-violet stripe bordered above by a wide black stripe. An identification key is provided for all the striped species of Meiacanthus, including at least one additional undescribed species previously confused with M. abditus. Color photographs of other Meiacanthus species and some new distributional records are also given.